2020
DOI: 10.1016/j.ebiom.2020.102982
|View full text |Cite
|
Sign up to set email alerts
|

Lipid laden macrophages and electronic cigarettes in healthy adults

Abstract: Background An outbreak of E-cigarette or Vaping Product Use-Associated Lung Injury (EVALI) with significant morbidity and mortality was reported in 2019. While most patients with EVALI report vaping tetrahydrocannabinol (THC) oils contaminated with vitamin E acetate, a subset report only vaping with nicotine-containing electronic cigarettes (e-cigs). Whether or not e-cigs cause EVALI, the outbreak highlights the need for identifying long term health effects of e-cigs. EVALI pathology includes alve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Shields et al, showed high LLM in the lungs of all conventional smokers and e-cigarettes users, however LLM presence in vape pen users was further associated with elevated levels of the inflammatory cytokines IL-4 and IL-10 in bronchoalveolar lavage fluid. [12] Vitamin E acetate is a thickening chemical agent which is used in THC containing products. Blount et al [13] showed Vitamin E in 94% of patients with THC associated EVALI, an experimental study [14] in rodents has shown EVALI symptoms without the use of THC, vitamin E or nicotine use.…”
Section: Discussionmentioning
confidence: 99%
“…Shields et al, showed high LLM in the lungs of all conventional smokers and e-cigarettes users, however LLM presence in vape pen users was further associated with elevated levels of the inflammatory cytokines IL-4 and IL-10 in bronchoalveolar lavage fluid. [12] Vitamin E acetate is a thickening chemical agent which is used in THC containing products. Blount et al [13] showed Vitamin E in 94% of patients with THC associated EVALI, an experimental study [14] in rodents has shown EVALI symptoms without the use of THC, vitamin E or nicotine use.…”
Section: Discussionmentioning
confidence: 99%
“…EVALI pathology was associated with alveolar damage and the presence of lipid-laden macrophages from BAL samples, suggestive of a pathologic role for AMs in the disease (Ref. 56).…”
Section: Environmental Insultsmentioning
confidence: 97%
“…Hence, neither short-term improvements nor the relatively milder changes in some parameters with e-cigarettes versus combustible cigarettes imply unalloyed harm reduction. As reported by several investigators [ 43 •, 100 ••, 104 ], the nature and the type of tissue injury inflicted by e-cigarettes are distinct from that caused by combustible cigarettes. For instance, even though in animal models, e-cigarettes, unlike combustible cigarettes, do not cause emphysematous changes, they stimulate the accumulation of lipid-laden macrophages, which could lead to dysregulation of the pulmonary surfactant and thereby compromise air-exchange and alter innate immunity [ 100 ••], pathological changes distinct from those seen with combustible cigarettes.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…Similar lipid-laden macrophages have also been detected in the BAL fluid of EVALI patients [ 103 ]. Although such lipid-laden macrophages have also been found in the lung of smokers, in e-cigarette users, these macrophages are associated with inflammatory cytokines such as IL-4 and IL-10, but not with smoking-related cytokines [ 104 ], suggesting that the pathophysiological changes induced by e-cigarettes in macrophages may be different in nature from that afflicted by combustible cigarettes.…”
Section: E-cigarettes and The Immune Responsementioning
confidence: 99%